Safety and Efficacy of Devices Delivering Inhaled Antibiotics among Adults with Non-Cystic Fibrosis Bronchiectasis: A Systematic Review and a Network Meta-Analysis - Sofia Tejada; Sergio Ramírez-Estrada; Carlos G. Forero; Miguel Gallego; Joan B. Soriano; Pablo A. Cardinal-Fernández; Stephan Ehrmann; Jordi Rello (MDPI AG, 2022)
It remains unknown whether the type of aerosol generating device is affecting efficacy and safety among non-cystic fibrosis bronchiectasis (NCFB) adults. The proposal of this network meta-analysis (NMA) is to evaluate effectiveness and safety of inhaled antibiotics administered via dry powder inhaler (DPI) and via nebulizers (SVN) among adult patients with NCFB. Inclusion criteria were randomized-controlled trials, adults (≥18 years) with NCFB, and inhaled antibiotics administered via DPI as intervention. Search strategy was performed in PubMed, Web of Science, and Cochrane Library from 2000 to 2019. Sixteen trials (2870 patients) were included. Three trials (all ciprofloxacin) used DPIs and thirteen used SVN (three ciprofloxacin). Both DPI and SVN devices achieved similar safety outcomes (adverse events, antibiotic discontinuation, severe adverse events, and bronchospasm). Administration of ciprofloxacin via DPI significantly improved time to first exacerbation (87 days, 95% CI 34.3-139.7) and quality of life (MD −7.52; 95% CI −13.06 to −1.98) when compared with via SVN. No other significant differences were documented in clinical efficacy (at least one exacerbation, FEV1% predicted) and microbiologic response (bacterial eradication, emergence of new potential pathogens, and emergence of antimicrobial resistance) when comparing devices. Our NMA documented that time to first exacerbation and quality of life, were more favorable for DPIs. Decisions on the choice of devices should incorporate these findings plus other criteria, such as simplicity, costs or maintenance requirements.